A Study on the Alteration of Endoplasmic Reticulum Stress-related Proteins in Cyclophosphamide-induced Damage to Urothelium - Hemalatha R; Muthuraman N; Sandya Rani; Premila Abraham (Mazandaran University of Medical Sciences, 2023)
Background: Cyclophosphamide is widely prescribed as an anti-cancer drug and used as an immunosuppressant. Hemorrhagic cystitis is one of the common complications of cyclophosphamide intake. We hypothesized that endoplasmic reticulum stress-related proteins could be altered in urothelium treated with cyclophosphamide.  Objectives: We checked the effect of cyclophosphamide on the expression of various endoplasmic reticulum stress-related proteins in Vero cells.  Methods: We treated Vero cells with varying doses of cyclophosphamide and observed its viability in flow cytometry using propidium iodide staining. We looked for changes in the expression of endoplasmic reticulum stress-related proteins in Vero cells treated with cyclophosphamide by western blot technique.  Results: Cyclophosphamide at higher doses caused more death in Vero cells that could be attributed to an increase in apoptosis as evidenced by the changes in the morphology of cells and increased expression of endoplasmic reticulum specific caspase-12 proteins. Growth arrest/DNA damage 153 (GADD 153), one of the key transcription factors involved in the mediation of endoplasmic reticulum stress and apoptosis, was upregulated in Vero cells treated with cyclophosphamide. The protective effect of glucose-regulated protein GRP 78 against apoptosis was lost in Vero cells treated with a higher dose of cyclophosphamide, which is corroborated by decreased expression of GRP 78 in Vero cells treated with higher doses compared to Vero cells treated with lower doses of cyclophosphamide. Expression of disulfide isomerase protein, which guides misfolded proteins to fold properly, was downregulated in Vero cells treated with cyclophosphamide.  Conclusion: To summarize, our study showed an alteration in the expression of key endoplasmic reticulum stress-related proteins in Vero cells treated with cyclophosphamide.